Novel approaches to low leakage and area efficient VLSI Design - Izma, Tajrian; Barua, Parag; Rahman, Md. Rejaur; Sengupta, Prianka (BRAC University, 2011)
his thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.